2021
DOI: 10.18488/journal.61.2021.93.550.567
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Metacognitive Skills towards the Retention of Different Academic Ability Students for the Implementation of Several Learning Models

Abstract: Metacognitive skills are self-regulation activities required to achieve active learning, critical thinking, problem solving, and decision making. There is a dearth of research on the contribution of metacognitive skills for the retention of students with varying academic abilities. This research study aims to fill this gap by suggesting learning models including READS (Reading, Exploring, Answering Discussing and Summarizing) learning model, Reading, Questioning and Answering (RQA) learning model and Conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…First, the Technology Acceptance Model was proposed by a professor at the School of Education of Stanford University in 1989 [10]. The model believes that when there is a certain distance between technology and users, users will have resistance.…”
Section: Theoretical Basis and Research Hypothesismentioning
confidence: 99%
“…First, the Technology Acceptance Model was proposed by a professor at the School of Education of Stanford University in 1989 [10]. The model believes that when there is a certain distance between technology and users, users will have resistance.…”
Section: Theoretical Basis and Research Hypothesismentioning
confidence: 99%
“…However, several studies (e.g., (Maccann et al, 2020;Perikova & Bysova, 2018)) about L2 metacognitive reading strategies indicate that there is a positive correlation between metacognitive awareness of readers and their success in L2 reading comprehension and performance. Moreover, it has been demonstrated that reading proficiency and second language overall proficiency are related to improving the metacognition of readers (Anderson, 2002;Sheorey & Mokhtari, 2001;Usman, Susilo, Suwono, & Corebima, 2021). Besides, it has been suggested that more skilled readers are highly aware of their metacognitive knowledge than less skilled ones (Phakiti, 2003).…”
Section: Metacognitive Reading Strategiesmentioning
confidence: 99%
“…PBLRQA can be applied in schools because it is problem-based, involves problem-solving thinking activities, and correlates with students' abilities. PBLRQA increases learning motivation, potentially empowering metacognitive skills and improving student retention [44].…”
Section: Introductionmentioning
confidence: 99%